PENGARUH RANSUM BERKADAR PROTEIN KASAR BERBEDA TERHADAP JUMLAH ERITROSIT, KADAR HAEMOGLOBIN, DAN HEMATOKRIT ITIK JANTAN - Zulkarnain Ronny Passya Reron; Rudy Sutrisna; Siswanto Siswanto (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This study aims to look at the number of erythrocytes, hemoglobin, and hematocrit drake of Mojosari Ducks given ration different levels of crude protein. This study was conducted three months from September 2015 to November 2015 held at the Laboratory of Animal Nutrition and Feed and enclosure Integrated Laboratory of the University of Lampung. Number of male ducks were used as many as 48 animals with 16 plots the number of cages, with each needs plots containing three male ducks. The process of data collection and research carried out at the end of each treatment taken one male ducks only. The experimental design used is Design Group. Grouping based on body weight. In the first group with body weight (150-175 g), second group (176-200 g), third group (201-225), fourth group (300-324). Ducks were divided into four treatment diets with different crude protein content, 16, 18, 20, 22%. Based on the results of this study concluded that the levels of crude protein ration was not significantly different (P> 0.05) to the number of erythrocytes, hemoglobin, and hematocrit drake. Keywords : Mojosari Ducks , Crude Protein , Erythrocytes , Hemoglobin , Hematocrit